Operationalising Governance and Technical Readiness for Federated Analytics: Findings from the PANORAMA Project - O'Sulivan, Katherine; Dahl, Astrid; Bishop, Katherine; Kotsagiannidis, Petros; Baswana, Kavya; Pallister, Diane; Duckworth, Helen; Bagnall, Alan; Waywell, Phil (International Journal of Population Data Science, 2026)
The PANORAMA project, a DARE UK TREvolution Early Adopters Programme, explored whether three NHS Secure Data Environments (SDEs) in the North of England could establish the foundations for federated analytics through shared governance, operational alignment, and emerging technical tools. The project comprised three technical work packages examining (1) the use of the SATRE specification to support a federated information governance (IG) framework, (2) the technical feasibility of using 5Safes TES to support federated analytics, and (3) SACRO (Semi-Automated Checking of Research Outputs) to to federated output checking, with robust public and professional consultation. PANORAMA demonstrates that meaningful federation requires a combination of organisational, governance and technical readiness, none of which are yet fully mature. First, technical tools designed to support federation—such as federated analytics and semi-automated output-checking—remain in active development. Partners emphasised the need for solutions that are stable, end-to-end, and “plug-and-play” to minimise burden on TRE operations teams and researchers. Second, federated information governance requires substantial professional oversight, the establishment of a shared vocabulary, and clear specifications of tolerance and equivalence between organisations. Public views broadly supported federated research, but had concerns over data security - which should be considered across all aspects of federation. Finally, the project highlighted that operationalising cross-organisation ways of working—spanning IG teams, technical staff, and research support—requires sustained coordination, central oversight, and ongoing monitoring. Federation is therefore achievable but dependent on maturing technical tools, finding equivalence to establish shared governance processes, and embedding continuous joint operational assurance.